STRATEGI PENGEMBANGAN USAHA KECIL DALAM MENINGKATKAN PENDAPATAN PEDAGANG KELAPA MUDA (Cocos Nucifera L) (Studi Kasus : Kecamatan Medan Kota, Kelurahan Teladan Barat) - Nia Aldina Lubis; Gustami Harahap; Mitra Musika Lubis (Universitas Medan Area, 2021)
This study aims to determine the Small Business Development Strategy in Increasing the Income of Young Coconut Traders (Cocos Nucifera L) (Case Study: Medan Kota District, Teladan Barat Village). Theobjectives of this study were: (1) to determine the income earned from small coconut traders inMedan City, Teladan Barat Village. (2) This is to determine the strategy for developing young coconutsmall traders in Medan City, Teladan Barat Village. This research was conducted in October-november2019. In this study the samples were taken based on the criteria, namely only entrepreneurs who hadyoung coconut ice-based businesses from a population of 24 entrepreneurs, only 17 entrepreneurs.This research method is descriptive with primary data sources obtained from distributingquestionnaires to respondents. The results of this study: (1) From the results of the researcher's calculationson the Young Coconut Ice business with an R / C ratio of 1.35 more than one. The income earned is Rp.103,000, - from the average total income of Rp. 390,000, - divided by the average cost of the sales process of Rp. 287,000. (2) Based on the results of research on business development strategies,it is a strategic choice made by entrepreneurs in Medan Kota sub-district, western exemplary villageto seize market opportunities. Entrepreneurs can gain a higher competitive advantage than theircompetitors if they can provide a selling price that is cheaper than the price given by its competitors with the same value or product quality.